Pengetahuan Ibu dan Pengobatan Mandiri untuk Batuk Balita: Studi Cross-Sectional di Apotek di Wilayah Tangerang (2024) - Erlia Anggrainy Sianipar; Lidya Himawan; Sherly Tandi Arrang (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Cough is a common symptom among toddlers, triggered by factors such as air pollution, weather changes, and allergies. In Tangerang, the prevalence of coughs in toddlers is notably high, leading many mothers to self-medicate their children. This study aims to assess the relationship between the mothers' knowledge and their self-medication behavior for treating toddler coughs at a pharmacy in Tangerang. This analytical observational study used a cross-sectional study involving 80 respondents. The data were collected through questionnaires, and univariate analysis was conducted to determine the frequency distribution of respondents by age, education, occupation, and sources of information regarding self-medication. Bivariate analysis using the Chi-Square method was employed to examine the relationships between these variables. The study found that most respondents were aged 18-44 years, with 38% having completed high school, 81.25% working as housewives, and 42.5% receiving information about self-medication from healthcare professionals. Despite 62.5% of the respondents having low knowledge about cough self-medication, 60% of them exhibited positive self-medication practices for treating coughs in toddlers. The analysis revealed no significant relationship between the mothers' knowledge levels and their self-medication behavior. In conclusion, the majority of mothers at Apotek Bintang Tangerang possess limited knowledge about self-medicating toddler coughs, yet they demonstrate positive self-medication behavior. Additionally, there is no significant correlation between their knowledge level and their behavior.